2015
DOI: 10.22495/cocv12i4csp12
|View full text |Cite
|
Sign up to set email alerts
|

Risk management practices in the top 20 South Africa’s listed companies: An annual/ integrated report disclosure analysis

Abstract: The King III Report on Corporate Governance places risk management at the nerve centre of the company’s strategic decision makers. The main objective of this article was to assess the risk management disclosures in the annual (integrated) reports of the top twenty (20) listed companies. The objectives were obtained through a literature review on risk management developments as per the requirements of the King III report on Corporate Governance, and supported by empirical evidence obtained from assessing the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Subsequent studies (Shuro 2014;Moloi 2014;PWC 2013PWC -2017Joubert 2014;Ungerer 2013) are shown in Table 2 as post-King III. The highest and lowest numbers of elements reported suggest that great variation exists between the companies' environmental disclosures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent studies (Shuro 2014;Moloi 2014;PWC 2013PWC -2017Joubert 2014;Ungerer 2013) are shown in Table 2 as post-King III. The highest and lowest numbers of elements reported suggest that great variation exists between the companies' environmental disclosures.…”
Section: Resultsmentioning
confidence: 99%
“…Only the overall results are shown in the section that follows. To determine any trends after the release of King III, the results of more recent studies (Shuro 2014;Moloi 2014;PWC 2013PWC -2017Joubert 2014;Ungerer 2013) are included in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers such as Erdener and Dunn (1990), Jauch, Osborn and Martin (1980), Mangena (2004), Barac and Moloi (2009), Barac, Marx and Moloi (2011), Moloi (2014 have all supported the use of content analysis method in extracting information by a way of coding and they all agree that content analysis has been growing in the course of the past decades and has now become an accepted research methodology in the social and business studies. For Holsti (1969) and Weber (1990) there are validity and reliability concerns on the manner in which content analysis method is used.…”
Section: Discussion Of Risk Management In South Africa's Public Servicementioning
confidence: 99%